First-Price Auctions in Online Display Advertising. (October 2021) - Despotakis, Stylianos; Ravi, R.; Sayedi, Amin
The authors link the rapid and dramatic move from second-price to first-price auction format in the display advertising market, on the one hand, to the move from the waterfalling mechanism employed by publishers for soliciting bids in a preordered cascade over exchanges to an alternate header bidding strategy that broadcasts the request for bid to all exchanges simultaneously, on the other. First, they argue that the move from waterfalling to header bidding was a revenue-improving move for publishers in the old regime when exchanges employed second-price auctions. Given the publisher move to header bidding, the authors show that exchanges move from second-price to first-price auctions to increase their expected clearing prices. Interestingly, when all exchanges move to first-price auctions, each exchange faces stronger competition from other exchanges, and some exchanges may end up with lower revenue than when all exchanges use second-price auctions; yet all exchanges move to first-price auctions in the unique equilibrium of the game. The authors show that the new regime hinders the exchanges' ability to differentiate in equilibrium. Furthermore, it allows the publishers to achieve the revenue of the optimal mechanism despite not having direct access to the advertisers.